IMPACT NOISE ISOLATION OF FLOOR SYSTEMS USING PLASTERBOARD CEILING WITH AND WITHOUT PET WOOL - Willian Magalhães de Lourenço; Gihad Mohamad; Eduardo Henrique Lucca Santos; Camila Taciani Rossi; Gabriela Meller (Mix Sustentável)
The acoustic insulation against impact noise of two floor systems was evaluated, using plasterboard lining installed under a prefabricated ribbed slab with prestressed joists, combined with PET wool in the lining. The tests followed the requirements of the ISO 16283-2 standard (ISO, 2020), and the data in accordance with the ISO 717-2 standard (ISO, 2020). Performance was classified by the values of the L'nT,w results established in the Brazilian standard NBR 15575-3 (ABNT, 2021). The flooring systems were composed of ceramic floors, vinyl floors, laminated wood floors and mechanical decoupling of the subfloor with glass wool and recycled rubber. Two situations were tested, with plasterboard lining (150 mm gap), and the second with filling the gap with 50 mm PET wool. From the experiments it was possible to conclude that the placement of 50 mm of PET wool blanket in the gap improved impact noise isolation by up to 3 dB, only in systems where there is no mechanical decoupling. Note that the better the impact noise insulation of the flooring system without PET wool in the lining, the less efficient the placement of this fibrous material will be.